The effectiveness of Microsoft Project in assessing extension of time under PAM 2006 standard form of contract - Suhaida @ Suhana, Kamarudin Nurul Aini Osman* (IOP Publishing, 2017)
Time is equal to money; and it is applies in the construction industry where time is very important. Most of the standard form of contracts provide contractual clauses to ascertain time and money related to the scenarios while Extension of Time (EOT) is one of them. Under circumstance and delays, contractor is allow to apply EOT in order to complete the works on a later completion date without Liquidated Damages (LD) imposed to the claimant. However, both claimants and assessors encountered problems in assessing the EOT. The aim of this research is to recommend the usage of Microsoft Project as a tool in assessing EOT associated with the standard form of contract, PAM 2006. A quantitative method is applied towards the respondents that consisted of architects and quantity surveyors (QS) in order to collect data on challenges in assessing EOT claims and the effectiveness of Microsoft Project as a tool. The finding of this research highlighted that Microsoft Project can serve as a basis to perform EOT tasks as this software can be used as a data bank to store handy information which crucial for preparing and evaluating EOT.